MO899: The Clinical frailty Scale is Useful for ICU Triage in Dialysis Patients With COVID-19–An Eracoda Analysis. (3rd May 2022) - Bouwmans, Pim; Brandts, Lloyd; Hilbrands, Luuk; Duivenvoorden, Raphael; Vart, Priya; Franssen, Casper; Jager, Kitty J; Noordzij, Marlies; Gansevoort, Ronald; Hemmelder, Marc
Abstract: BACKGROUND AND AIMS: during the COVID-19 pandemic, several guidelines have recommended the use of the Clinical Frailty Scale (CFS) for triage of critically ill patients with COVID-19 in case of shortage in ICU resources. However, no data on using CFS assessment for ICU triage for dialysis patients is yet available. This study evaluates whether CFS is associated with mortality rates in a cohort of hospitalized dialysis patients with COVID-19. METHOD: the analyses are based on data of the European Renal Association COVID-19 Database (ERACODA). Dialysis patients who presented with COVID-19 between 1 February 2020 and 30 April 2021 and with complete information on CFS and vital status at 3 months were included. Study outcomes were hospital and ICU admission rates and hospital and ICU mortality at 3 months after hospital admission. Cox regression analyses were performed to assess the association of CFS category (≤5 versus ≥ 6) and study outcomes in line with Dutch ICU triage guidelines for COVID-19. Furthermore, additional subgroup analyses were performed to assess the association between CFS and 3-month mortality by age category (<65, 65–75 and >75 years). RESULTS: among a total of 2206 dialysis patients (mean age = 67.2 (14.1) years, male sex = 61%), 1694 (77%) had CFS ≤ 5 and 514 (23%) had CFS ≥ 6. Hospitalization rate was comparable in patients with CFS ≤ 5 and in patients with CFS ≥ 6 (67 and 71%, respectively), whereas the rate of ICU admission was higher in patients with CFS ≤ 5 than in patients with CFS ≥ 6 (16 versus 9%, p = 0.001). Among 1501 hospitalized patients, 3-month mortality was 26% of patients with CFS ≤ 5 and 59% in patients with CFS ≥ 6 ( P < 0.001). Multivariate analysis with adjustment for patient demographics, smoking status and BMI revealed that CFS ≥ 6 was associated with hospital mortality [aHR 2.27 (1.88–2.74) versus CFS ≤ 5; P < 0.001) with a significant interaction for age ( P = 0.029). aHR was 4.00 (2.56–6.37; CFS ≥ 6 versus CFS ≤ 5; P < 0.001) in patients < 65 years, aHR was 1.87 (1.33–2.64; CFS ≥ 6 versus CFS ≤ 5; P < 0.001) in patients 65–75 years and aHR was 2.12 (1.64–2.75; CFS ≥ 6 versus CFS ≤ 5; P < 0.001) in patients >75 years. Among 219 ICU admitted patients, 3-month mortality was 60% of the patients with CFS ≤ 5 and 91% in the patients with CFS ≥ 6, respectively. Multivariate analysis with adjustment for patient demographics, smoking status and BMI revealed that CFS ≥ 6 was associated with ICU mortality [aHR 1.80 (1.17–2.77); CFS ≥ 6 versus CFS ≤ 5; P = 0.002]. CONCLUSION: more frail dialysis patients with CFS ≥ 6 who are hospitalized for COVID-19 were less often admitted to the ICU, but in case they were admitted to the ICU they have a very high mortality of 91% in this cohort study. In fit to mildly frail dialysis, patients who were admitted to the ICU, mortality rates are lower. The association between frailty and hospital mortality is interacted by age with the strongest association in patients younger than 65 years. These findings suggest that CFS may be a useful complementary triage tool for ICU admission of dialysis patients during the ongoing COVID-19 pandemic.